2012
DOI: 10.5120/4579-6755
|View full text |Cite
|
Sign up to set email alerts
|

Real Time Dynamic State Estimation for Power System

Abstract: This paper investigates a method for the state estimation of nonlinear systems described by a class of differentialalgebraic equation (DAE) models using the extended Kalman filter. The method involves the use of a transformation from a DAE to ordinary differential equation (ODE). A relevant dynamic power systems model using decoupled techniques will be proposed. The estimation technique consists of a state estimator based on the EKF technique as well as local stability analysis. High performances are illustrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The diagram of simulation used for implementation under Simulink of MATLABr and using the toolbox SimPowerSystems with Powereguir is given in [11] with more details. Now, in the first case (case 1), the defect is a solid three-phase fault to ground applied at time 3 s in node 3.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagram of simulation used for implementation under Simulink of MATLABr and using the toolbox SimPowerSystems with Powereguir is given in [11] with more details. Now, in the first case (case 1), the defect is a solid three-phase fault to ground applied at time 3 s in node 3.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The existing dynamic models treated in differential-algebraic equation (DAE) systems are simplified by linearization [8] or considered as a reduced swing model [9]. We have shown that we can always rewrite the system with a nonlinear DAE form with explicit ordinary differential equation (ODE) to facilitate its implementation and operation [11]. We have shown that we can always rewrite the system with a nonlinear DAE form with explicit ordinary differential equation (ODE) to facilitate its implementation and operation [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transit power is considered as measurements (we have used the toolbox SimPowerSystems of MATLAB to generate the actual measurements [20]). For the discretizat ion of the model (09), we have used Euler d iscretization with a step size …”
Section: Simulation Resultsmentioning
confidence: 99%
“…As no universal approach exists, state observers, in particular for nonlinear systems, are still a challenging and open problem. Beside the famous extended Kalman filter [14] [4] [5] (and its real time application with DSP device [15]), we distinguish a simple and useful nonlinear state observer based on the solution of a Riccati-like equation and the Lipschitz condition [12] [20] [11].…”
Section: Introductionmentioning
confidence: 99%